2021
DOI: 10.7717/peerj.12714
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram-derived pain index for evaluating pain during labor

Abstract: Background The discriminative ability of a point-of-care electroencephalogram (EEG)-derived pain index (Pi) for objectively assessing pain has been validated in chronic pain patients. The current study aimed to determine its feasibility in assessing labor pain in an obstetric setting. Methods Parturients were enrolled from the delivery room at the department of obstetrics in a tertiary hospital between February and June of 2018. Pi values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 11 The development of the DELi score was based on the entire frequency band-EEG wavelet algorithm. 12 , 13 In the presence of delirium, repeatable and regular changes were extracted from brain waves as the characteristic indicators of delirium. 14 The DELi score incorporated these dynamic variations of EEG parameters attributable to delirium based on a wavelet algorithm, 12 , 13 and was thus related to the cognitive status of delirium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 The development of the DELi score was based on the entire frequency band-EEG wavelet algorithm. 12 , 13 In the presence of delirium, repeatable and regular changes were extracted from brain waves as the characteristic indicators of delirium. 14 The DELi score incorporated these dynamic variations of EEG parameters attributable to delirium based on a wavelet algorithm, 12 , 13 and was thus related to the cognitive status of delirium.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Recently, the entire frequency band EEG was analyzed by developing a wavelet analysis method. 12 , 13 Based on this wavelet algorithm, a series of specific changes in EEG were identified when delirium occurred. These dynamic variations of EEG parameters attributable to delirium were integrated into a real-time index named the delirium index (DELi ranging from 0-100 and positively associated with the probability of delirium).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the NRS showed similar variability to that of the VAS. Most interesting was the variability that occurred in the 9 studies 3,18,29,37,40,73,83,86,110 that included additional verbal descriptors beneath the tool, in relation to the terms used as well as the numerical values denoted to each (Fig. 3).…”
Section: Numerical Rating Scalementioning
confidence: 99%
“…For example, 1 study 37 used the descriptor "severe" for a rating of 10 out of 10, whereas another 18 used that same descriptor for any rating above 5 out of 10. Seven 3,29,37,73,83,86,110 of the 9 studies used the descriptor "nil" for a rating of zero out of 10, whereas 2 studies 18,40 denoted a rating of zero as either "mild" or "low" pain, thereby removing the possibility for the user to indicate no pain.…”
Section: Numerical Rating Scalementioning
confidence: 99%
“…However, the ndings were restricted by a small sample size (n = 10) and absent observations of EEG changes in uterine contraction pain following LEA. Sun et al [13] found that Pain Index (Pi), developed from EEG using two channels, could be utilised as a quantitative and objective measurement of labour pain. However, PI is a general measure that cannot pinpoint which brain regions or electrodes are most responsible for the EEG changes brought by labour pain.…”
mentioning
confidence: 99%